Pengembangan Acid-Base Multimedia (ABM) pada Pembelajaran Kimia untuk Memberdayakan Literasi Sains Peserta Didik - Suliono Suliono; Eny Enawaty; Indri Astuti (Jurnal Penelitian Pendidikan IPA, 2023)
This research is motivated by the importance of the process of empowering scientific literacy in constructing students' understanding of learning chemistry. This study aimed to determine the effectiveness of developing Acid Base Multimedia (ABM) in chemistry learning to empower students' scientific literacy. This research uses research and development methods. It is used 4D models, with definition, design, develop, and deploy stages. The study involved participants consisting of teachers and students in class XI MIPA at SMA Santo Paulus Pontianak. Development of Acid-Base Multimedia design through expert appraisal from media, design, and material experts obtained a score of 4.86; 4.72; 4.51; with a very valid category. The stages of development testing, obtained an average response rate of 4.71, 4.54, and 4.24, respectively, with a very good category. The N-gain score is 0.6028, which means that the interpretation of the level of influence of increasing test results from learning to use Acid Base Multimedia is moderate. Testing the effectiveness of Acid-Base Multimedia with effect size obtained a value of 2.2 in the strong effect category. Based on the results of the study, it can be concluded that Acid Base Multimedia can empower scientific literacy effectively in constructing students' understanding of acid-base material